THE IMPACT OF DEEP BREATHING COMBINED WITH AROMATHERAPY ON ANXIETY LEVELS IN PRE-CAESAREAN SECTION PATIENTS AT KERTHA USADA HOSPITAL - Ni Putu Diah Ayu Rusmeni; I Dewa Gede Agus Ardana Putra; Nurul Imam (Nurse and Holistic Care, 2025)
Background: Preoperative anxiety is commonly experienced by women undergoing caesarean section and may negatively affect physiological stability during surgery. Non-pharmacological interventions such as deep breathing, relaxation, and aromatherapy are considered effective strategies to reduce anxiety. Objective: This study aimed to examine the effect of a combination of deep breathing relaxation and aromatherapy on anxiety levels in patients undergoing preoperative caesarean section. Methods: This pre-experimental study employed a one-group pretest–posttest design and was conducted at Kertha Usada General Hospital, Buleleng, Indonesia, from April to May 2025. A total of 67 patients scheduled for caesarean section were recruited using consecutive sampling. Anxiety levels were assessed before and after the intervention using a standardized anxiety questionnaire. The intervention consisted of deep breathing relaxation combined with aromatherapy. Data were analyzed using the Wilcoxon signed-rank test. Result: The results showed a statistically significant reduction in anxiety levels after the intervention (p = 0.001; p < 0.05). Conclusion: The combination of deep breathing relaxation and aromatherapy effectively reduced preoperative anxiety in patients undergoing caesarean section and may serve as a complementary nursing intervention to enhance preoperative care.